1992
DOI: 10.1093/carcin/13.6.935
|View full text |Cite
|
Sign up to set email alerts
|

Genetic alterations in the 61st codon of the H-ras oncogene isolated from archival sections of hepatic hyperplasias, adenomas and carcinomas in control groups of B6C3F1 mouse bioassay studies conducted from 1979 to 1986

Abstract: In order to better understand the molecular events in murine hepatocarcinogenesis, the frequency and types of mutations in the murine H-ras proto-oncogene isolated from 184 independent, spontaneously occurring hepatic lesions were determined. Hepatocellular foci, hyperplasias, adenomas and carcinomas were obtained from archival samples of control male (134 samples) and female (50 samples) B6C3F1 mice used in oncogenicity studies that were conducted at Lilly Research Laboratories from 1979 to 1986. The 61st cod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

1997
1997
2000
2000

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 0 publications
0
14
0
Order By: Relevance
“…One molecular pathway of rat hepatocarcinogenesis induced by NNM has been classified using antisense techniques. Determination of mutation frequencies in hepatic lesions has proved that mutations in codon 61 of Ha-ras are early events in spontaneous murine hepatocarcinogenesis (Richardson et al, 1992). However, our data show that a mutated Ha-ras antisense oligonucleotide (AS-Leu) decreases cell proliferation in both preneoplastic lesions and hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 66%
See 3 more Smart Citations
“…One molecular pathway of rat hepatocarcinogenesis induced by NNM has been classified using antisense techniques. Determination of mutation frequencies in hepatic lesions has proved that mutations in codon 61 of Ha-ras are early events in spontaneous murine hepatocarcinogenesis (Richardson et al, 1992). However, our data show that a mutated Ha-ras antisense oligonucleotide (AS-Leu) decreases cell proliferation in both preneoplastic lesions and hepatocellular carcinomas.…”
Section: Discussionmentioning
confidence: 66%
“…In murine hepatic tumors, however, a single point mutation at codon 61 of Ha-ras is common. For example, Richardson et al (1992) examined genetic alterations in codon 61 of Ha-ras oncogenes isolated from archival sections of hepatic hyperplasias, adenomas and carcinomas in B6C3F1 mice, which have a high incidence of spontaneous liver tumors. They found that 41% of the carcinomas, 44% of the adenomas, 42% of the hyperplasias and 29% of the foci contained mutations in codon 61, being mostly CAA-CGA transversion, followed by CAA-CTA transversion.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The incidence and pattern of the mutations are similar to those in spontaneous benign and malignant hepatocellular tumors in some non-Tg mouse strains such as C3H and B6C3Fl. Mouse c-H-ras activation has been believed to be a relatively early event in spontaneous mouse liver carcinogenesis (6,15). Although the number of benign lesions examined in this study is not sufficient to draw any definite conclusion, the absence of mutations in the 4 foci of cellular alteration and in the 1 hepatocellular adenoma from rusH2 Tg mice may suggest that the occurrence of codon 61 point mutations is a late event in the progression of hepatocellular neoplasia in this Tg mouse.…”
Section: Discussionmentioning
confidence: 99%